The practical guide to achieving customer satisfaction in events and hotels - Berners, Philip; Martin, Adrian (London ; New York : Routledge, 2023)
"The Practical Guide to Achieving Customer Satisfaction in Events and Hotels is the 4th title in the Routledge Series The Practical Guide to Events and Hotel Management and presents expert-led insight of customer service best practice within events and hotels. This book is ideal for students of the management of events, hotels, hospitality or tourism, to be used as a practical resource alongside existing theoretical textbooks. It is also an essential tool for anybody working in the customer-facing industries"--
Includes bibliographical references and index.
Keywords: Hospitality industry -- Customer services; Hotel management; Special events -- Management